Autistic and dysphasic children differ in social responsiveness and empathy but not in systemizing behavior - Hrdlička, Michal; Urbánek, Tomáš; Mrkvička, Adam; Komárek, Vladimír; Pospíšilová, Lenka; Mohaplová, Markéta; Blatný, Marek; Dudová, Iva (Československá psychologie, 2023)
Objectives. The Social Responsiveness Scale (SRS) and the Empathizing/Systemizing Quotient (EQ/SQ) scale are both used for the assessment of individuals with autism spectrum disorder (ASD). This study aimed to investigate the use of both scales to assess another neurodevelopmental disorder, namely developmental dysphasia (DD). Additionally, we examined differences in social, empathetic, and systemizing characteristics between ASD and DD groups. Sample and settings. The authors examined 103 children with (1) ASD (n = 30, mean age 8.4 ± 2.6 years), (2) DD (n = 35, mean age 8.9 ± 2.3 years), and (3) healthy control children (HC; n = 38, mean age 9.2 ± 1.6 years) using the SRS and EQ/SQ assessments. Subjects with additional psychiatric diagnoses, e.g., intellectual disabilities and/or genetic syndromes, were excluded from the study. Statistical analysis. Descriptive statistics, one-way ANOVA, chi-square test, and Kruskal-Wallis test with the Bonferroni correction were used. Hypotheses. The null hypothesis was that there are no significant differences between the ASD, DD and HC subgroups on the Social Responsiveness Scale and on the Empathizing/Systemizing Quotients. Results. There were statistically significant differences on the SRS between the ASD, DD, and HC groups (97.0 vs. 52.0 vs. 29.0, p<0.001). Differences in EQ scores were also significant between the groups in total (17.0 vs. 30.0 vs. 35.0, p<0.001); however, post-hoc tests did not confirm a significant difference between the DD and HC groups. There were no statistically significant differences on the SQ score between the groups. Limitations. The gender imbalance of our subgroups and the relatively small sample size of our study were the main limitations of our study.